From general English to scientific literacy: a TBLT intervention for laboratory report writing among Thai EFL students - Sunai Singtong; Thapanee Khemanuwong; Ekkapon Phairot; Jarinya Srimanee; Tanassanee Jitpanich (Cogent Education, 2025)
This study investigated the effectiveness of task-based language teaching (TBLT) in enhancing Thai EFL high school students’ scientific laboratory report writing performance. Using a sequential mixed-methods pre-experimental design, 35 Grade 11 students from a science and mathematics program participated in an eight-week TBLT intervention that integrated focus-on-forms instruction within authentic laboratory report writing tasks based on chemistry experiments. Quantitative analysis using paired sample t-tests revealed statistically significant improvements from pretest (M = 16.58, SD = 3.74) to posttest (M = 27.18, SD = 3.58), with a large effect size (η2 = 0.81). The most substantial gains occurred in language style (η2 = 0.75), introduction (η2 = 0.74), and report format (η2 = 0.73). Qualitative findings from semi-structured interviews with eight purposively selected students identified key benefits of TBLT, namely enhanced writing practice opportunities, vocabulary expansion, improved analytical skills, and strengthened writing proficiency. Nonetheless, students also reported challenges related to heavy workload, complex content, and insufficient task clarity. The findings demonstrate TBLT’s potential for developing discipline-specific academic writing skills among EFL learners when combined with explicit form-focused instruction. This research contributes empirical evidence supporting TBLT implementation in scientific writing contexts and offers pedagogical insights for English language educators working with academically demanding genres in EFL settings.
Keywords: EFL/ESL Teaching and Learning; Second Language Learning and Teaching; Writing and Handwriting Education